A complex unit for a complex disease: the HCM-Family Unit - Vriz, Olga; AlSergani, Hani; Elshaer, Ahmed Nahid; Shaik, Abdullah; Mushtaq, Ali Hassan; Lioncino, Michele; Alamro, Bandar; Monda, Emanuele; Caiazza, Martina; Mauro, Ciro; Bossone, Eduardo; Al-Hassnan, Zuhair N.; et al. (Monaldi Archives for Chest Disease, 2021)
Hypertrophic cardiomyopathy (HCM) is a group of heterogeneous disorders that are most commonly passed on in a heritable manner. It is a relatively rare disease around the globe, but due to increased rates of consanguinity within the Kingdom of Saudi Arabia, we speculate a high incidence of undiagnosed cases. The aim of this paper is to elucidate a systematic approach in dealing with HCM patients and since HCM has variable presentation, we have summarized differentials for diagnosis and how different subtypes and genes can have an impact on the clinical picture, management and prognosis. Moreover, we propose a referral multi-disciplinary team HCM-Family Unit in Saudi Arabia and an integrated role in a network between King Faisal Hospital and Inherited and Rare Cardiovascular Disease Unit-Monaldi Hospital, Italy (among the 24 excellence centers of the European Reference Network (ERN) GUARD-Heart). Graphical Abstract